Handbook of human stress and immunity - Glaser, Ronald, 1939-; Kiecolt-Glaser, Janice K. (Academic Press, 1994)
In 1964, George Solomon coined the term psychoneuroimmunology. In the intervening 30 years, this term has emerged into a dynamic field of study which investigates the unique interactions between the nervous, endocrine, and immune systems. The Handbook of Human Stress and Immunity is a comprehensive reference for this dynamic new field. Focusing on how stressors impact the central nervous system and the resulting changes in immune responses, the Handbook is the first to describehow stress specifically affects human immune systems. It discusses how stress generally makes people more susceptible to infection, how personal support systems can counteract the physiological effects of stress, and how stress, or lack of stress, affects the aging process. Chapters are authored by the leading names in the field and cover such diseases as autoimmune disease, viral pathogenesis, herpes, HIV, and AIDS.